Optimal duration of a first-line palliative chemotherapy in disseminated colorectal cancer – a review of the literature from a developing country perspective - Rogowski, Wojciech; Sulżyc-Bielicka, Violetta (Contemporary Oncology/Współczesna Onkologia, 2016)
We still do not know whether the presently used protocol of the first-line palliative treatment of disseminated colorectal cancer (FOLFOX/FOLFIRI protocol) allows maximization of therapeutic response and minimization of side effects. No-one has verified whether continuation of the first-line chemotherapy despite the lack of progression is reflected by improved prognosis or significant risk of toxicity. This issue is of vital importance in the case of developing countries where targeted therapies are not available due to financial shortages. We have identified three potential strategies of the palliative therapy of disseminated colorectal cancer: 1) discontinuation of chemotherapy after a fixed number of cycles with its restart on progression (stop-and-go strategy), 2) intermittent protocol of chemotherapy, and 3) continuation of chemotherapy with discontinuation of the most toxic agent. None of the studies proved the superiority of the most commonly used standard, i.e. 12 cycles of the FOLFOX or FOLFIRI regimen. Although longer duration of this treatment may be associated with higher response rates and longer progression-free survival, these improvements frequently prove insignificant on statistical analysis.